2021
DOI: 10.1007/s11042-021-10980-3
|View full text |Cite
|
Sign up to set email alerts
|

PhyDSLK: a model-driven framework for generating exergames

Abstract: In recent years, we have been witnessing a rapid increase of research on exergames—i.e., computer games that require users to move during gameplay as a form of physical activity and rehabilitation. Properly balancing the need to develop an effective exercise activity with the requirements for a smooth interaction with the software system and an engaging game experience is a challenge. Model-driven software engineering enables the fast prototyping of multiple system variants, which can be very useful for exerga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Improved connectivity creates opportunities for more seamless social gameplay and remote rehabilitation interventions. No-or lowcode platforms could also lower the threshold so game development can become more rapid and widespread, as Baldassarre et al (2021) demonstrated. Lowering this threshold moves us closer to applying co-creation in the game design process and, thus, applicable applications.…”
Section: Technologymentioning
confidence: 99%
“…Improved connectivity creates opportunities for more seamless social gameplay and remote rehabilitation interventions. No-or lowcode platforms could also lower the threshold so game development can become more rapid and widespread, as Baldassarre et al (2021) demonstrated. Lowering this threshold moves us closer to applying co-creation in the game design process and, thus, applicable applications.…”
Section: Technologymentioning
confidence: 99%
“…The increasing divide between ease of use and game development speed using modern-day game engines (D. M. Hmeljak & Zhang, 2020) can make it difficult for a beginner to develop a game. This is where Model Driven Game Development (MDGD) approaches have been used by developers to reduce development time with reusable artifacts (Baldassarre et al, 2021;Marchisio, Margaria, & Sacchet, 2020;Reyno & Carsí Cubel, 2009). One cannot predict how long it can take to build a new component or if it will be implemented in the final game.…”
Section: Related Workmentioning
confidence: 99%